Natural antifungal systems for prevention of mould spoilage in bakery products - Arroyo, Mariona (Cranfield University, 2003)
Growth of spoilage fungi in bread and other bakery products is currently controlled with the addition of weak acid preservatives. Consumers demand more natural products and thus there is a need to reduce the amount of chemical preservatives added to foods, or to identify alternative, more 'natural' antifungal compounds with strong biological activity. This thesis reports on several areas of research undertaken in the project: evaluation of sub-optimal concentrations of existing preservatives, under different environmental conditions, on growth and ochratoxin A (OT A) production by six bread spoilage moulds; efficacy of new/natural antifungal compounds for possible use in bread preservation; evaluation of the impact of preservation hurdles on ecophysiology of the spoilage fungi, including niche overlap; and mechanisms of action of preservatives on hydrolytic enzymes. It was found that the use of currently applied levels of the existing preservatives potassium sorbate, calcium propionate and sodium benzoate were effective, under low pH environments (pH 4.5) at completely controlling growth of spoilage moulds (Aspergillus ochraceus, Eurotium repens, Cladosporium herbarum, Penicillium corylophilum and Penicillium verrucosum) on wheat flour-based substrates over a period of 30 days. At higher pH levels, the efficacy decreased being almost nil at pH 7.5. The use of sub-optimal concentrations of weak acid preservatives led in most cases to reductions in lag times and/or stimulation of mould growth and ochratoxin A production by P. verrucosum strains. Cont/d.